Cooperative Learning In Improving Students' Collaborative - Daiyah, Aswai'; Ramadhani, Gia Syauqiyah; Farhurohman, Oman (Indonesian Journal of Elementary Education (IJEE), 2024)
This study discusses how cooperative learning strategies can help students work better together in teams. Using a literature review and descriptive qualitative methods, this study looks at theories, models, and challenges in cooperative learning. The results show that cooperative learning can improve social skills, make students more engaged, and encourage shared responsibility in teams. Some learning models, such as Jigsaw, STAD, and TGT, are mentioned as effective ways to help students understand lessons, work well together, and improve their communication skills. This article also discusses the challenges of implementing this method in the classroom as well as solutions such as teacher support and choosing the right learning model.Keywords: Cooperative Learning, Collaborative Skills, Education.